Implementation of Rocket Stove–Based Drying Technology to Improve Local Food Processing Productivity in Teniga Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Teniga Village has abundant banana resources, and low market prices have encouraged the community to add value through food processing. The Kembang Pisang Group, established in 2021 with 20 members, is one of the leading community groups engaged in the production of pisang sale (dried bananas). Before the technological intervention, the drying process relied solely on traditional sun drying, which made it highly dependent on weather conditions, required 4-7 days, and often resulted in mould growth and inconsistent product quality. The community empowerment program, implemented to address these challenges, consisted of a situation analysis, socialization, training, and evaluation. The application of rocket-stove hybrid drying technology has had significant impacts. Before its implementation, the total production volume was only 15 kg; it increased to 40 kg, representing a 166% improvement. Reduced drying time and increased production volume are key indicators of successful productivity enhancement in local banana-based food products in Teniga Village.